Strategy and Business Plan for the Pakistan Infrastructure Project Financing Facility : Infrastructure Financing Market Update - World Bank (Washington, DC, 2013)
The report presented a detailed assessment of the infrastructure Public Private Partnership (PPP) financing market in Pakistan, including key financing gaps as existent in 2007. This note builds on the report by presenting an update of the state of the Pakistan infrastructure financing market as on date, and in particular, by analyzing the implications of the global financial crisis and the changes in the macroeconomic environment in Pakistan. This note is structured as follows: section two provides background information on the Pakistan economy; section three summarizes the key effects of international financial shocks and domestic political issues on the Pakistan economy; section four summarizes the progress on the infrastructure enabling environment; section five provides a summary update of the demand for infrastructure finance; section six presents recent developments in the supply of infrastructure finance; and section seven sets out the key conclusions.